The Influence of the 5S Concept on Auditor Work Productivity (Survey of the IIndonesian Financial Audit Agency) - Yori Naufal Shalihan; Antonius Setiadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The Supreme Audit Agency, in carrying out its main function of auditing, still encounters instances where audit procedures cannot be completed on time by the auditors. The 5S concept is expected to offer a solution to ensure that audit procedures are completed on time, and it is therefore proposed that this concept be implemented in the institution to improve auditor work productivity. This study analyzes whether the 5S concept has an impact on auditor work productivity, using a sample of 100 respondents analyzed with Smart PLS version 4.0. The results show that the statistical values for